Targeted NMDA receptor knockdown in recall‐activated neuronal ensembles impairs remote fear extinction - Yongmin Sung; Dae Hee Han; Junhyuk Kim; Pojeong Park; Bong-Kiun Kaang (Molecular Brain)
Abstract Fear extinction training in rodents decreases fear responses, providing a model for the development of post-traumatic stress disorder therapeutics. Fear memory recall reactivates the consolidated fear memory trace across multiple brain regions, and several studies have suggested that these recall-activated neurons are re-engaged during extinction. However, the molecular mechanisms linking this reactivation to extinction remain largely elusive. Here, we investigated the role of N-Methyl-d-Aspartate receptors (NMDARs) in remote memory recall–activated neurons within the basolateral amygdala and the medial prefrontal cortex during extinction training in mice. We found that Grin1 knockdown in these specific ensembles impaired extinction of remote fear memory, but did not reduce their reactivation during retrieval of the extinguished memory. These data suggest that while reactivation of these neuronal populations persists, their NMDARs are crucial for driving the synaptic plasticity needed to extinguish remote fear memories.